2003
DOI: 10.1007/s00421-002-0741-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of plyometric training on distance running performance

Abstract: Previous research has reported that plyometric training improves running economy (RE) and ultimately distance-running performance, although the exact mechanism by which this occurs remains unclear. This study examined whether changes in running performance resulting from plyometric training were related to alterations in lower leg musculotendinous stiffness (MTS). Seventeen male runners were pre- and post-tested for lower leg MTS, maximum isometric force, rate of force development, 5-bound distance test (5BT),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
369
7
35

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(432 citation statements)
references
References 28 publications
21
369
7
35
Order By: Relevance
“…Although both HRT and PRT results are in accordance with growing literature demonstrating that heavy resistance-training or plyometric training improved the running economy of welltrained athletes ( (15,25,33,36,42,43,46,48), the magnitude of enhancements were lower in our study compared to previous studies reporting effects following heavy-resistance (15,25,33,46) or plyometric training (36, 42,43,48). This could be due to different phases of season that the studies were performed.…”
Section: A C C E P T E Dsupporting
confidence: 88%
See 3 more Smart Citations
“…Although both HRT and PRT results are in accordance with growing literature demonstrating that heavy resistance-training or plyometric training improved the running economy of welltrained athletes ( (15,25,33,36,42,43,46,48), the magnitude of enhancements were lower in our study compared to previous studies reporting effects following heavy-resistance (15,25,33,46) or plyometric training (36, 42,43,48). This could be due to different phases of season that the studies were performed.…”
Section: A C C E P T E Dsupporting
confidence: 88%
“…Previous studies (17,36,43) have reported that various forms of resistance training may lead to improved endurance performance in trained subjects. However, the optimal prescription of resistance training to improve endurance running performance has yet to be firmly established.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Consequently, for moderately trained individuals used within the study, there b b b ' merely reflect a reduction in perceived exertion and improved thermal comfort under heat stress. Previous studies investigating various interventional strategies on 3 km performance, include intermittent hypoxic (Stray-Gundersen, et al, 2001;Katayama, et al, 2003Katayama, et al, , 2004Rodriguez et al, 2007), plyometric (Spurrs et al, 2003;Pellegrino et al, 2015) and intense training periods (Smith et al, 1999;Coutts, et al, 2007;Esfarjani, et al, 2007), reporting a vast range in improvements from 0.8 to 7.3%. However, the le ' aerobic fitness level, running experience, length and method of intervention vary considerably and so comparisons to this study must be interpreted lightly.…”
Section: 4mentioning
confidence: 99%